Post-infantile giant cell hepatitis: histological and immunohistochemical study. Issue 11 (November 1994) - Johnson, S J; Mathew, J; MacSween, R N; Bennett, M K; Burt, A D
Abstract : AIM--To determine the composition of the inflammatory infiltrate and to check for the presence of cytomegalovirus (CMV) and Epstein-Barr virus (EBV) in nine cases of post-infantile giant cell hepatitis. METHODS--The clinical, serological, and histological features of the nine cases were reviewed. Immunohistochemistry was used on liver biopsy specimens from six cases to: (i) characterise the lymphocytic infiltrate; (ii) assess the monocyte/macrophage response; (iii) detect "activated" perisinusoidal cells; and (iv) detect CMV and EBV antigens. Electron microscopic examination was carried out in two cases. RESULTS--Four patients had serological features suggestive of autoimmune chronic active hepatitis; in the other five cases the aetiology was obscure. Two patients presented with neurological symptoms. Hepatitis resolved completely in one patient; two patients showed clinical improvement; and one remained stable. Cirrhosis developed in three patients, one of whom proceeded to liver transplantation, and three patients died. Portal inflammation was present in all cases and lymphocytic piecemeal necrosis in eight cases, but intra-acinar inflammation associated with hepatocyte necrosis was observed in only five cases. The inflammatory infiltrate was composed predominantly of T lymphocytes; an increase in monocyte/macrophage cells was also observed. Mallory bodies, often with associated neutrophilic infiltrate, were present in four cases, and bilirubinostasis was a feature in four cases. "Activated" perisinusoidal cells were present, especially in relation to areas of inflammation, necrosis, and fibrosis. There was severe fibrosis or cirrhosis in five cases. Paramyxoviral nucleocapsids were not seen in the two cases examined ultrastructurally. CONCLUSIONS--Post-infantile giant cell hepatitis should be viewed as a heterogeneous clinical and aetiological entity encompassing cases of hepatitis with extensive giant cell hepatocyte transformation.